The analysis of Organizational Communication Climate at the One Door Integrated Service and Investment Department (DPM-PTSP) City of Makassar - Muh Ramlan Febriansyah; A. Alimuddin Unde; Arianto Arianto (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to determine the organizational communication climate at the Office of Investment and One Stop Services (DPM-PTSP) Makassar City. This study involved 40 employees who performed public services for the last 3 months at the Makassar City Investment and One Stop Integrated Service (DPM-PTSP) office. This study uses a quantitative approach with data collection techniques using a questionnaire made using a Likerts scale. Data were analyzed using SPSS and MS Excel. The results showed that the organizational communication climate showed results with an average value of 112 which indicated the organizational communication climate at the Makassar City DPM-PTSP office was categorized as Good Enough.